A Kantian Defense of Abortion Rights with Respect for Intrauterine Life - Manninen, Bertha Alvarez (Diametros, 2014)
In this paper, I appeal to two aspects of Immanuel Kant’s philosophy – his metaphysics and ethics – in defense of abortion rights. Many Kantian pro-life philosophers argue that Kant’s second principle formulation of the categorical imperative, which proscribes treating persons as mere means, applies to human embryos and fetuses. Kant is clear, however, that he means his imperatives to apply to persons, individuals of a rational nature. It is important to determine, therefore, whether there is anything in Kant’s philosophy that permits regarding embryos and fetuses as persons, since they lack the capacity for sentience (at least until mid-gestation), let alone rational thought. In the first part of the paper, I will illustrate why there are difficulties maintaining, from a Kantian perspective, that conception marks the genesis of a new person. Even granting that embryos and fetuses are persons, however, this alone would not entail the moral impermissibility of abortion rights, mainly because prohibiting abortion, and compelling women to gestate, violates the formula of humanity against them. Developing this thesis encompasses the second part of my essay. Finally, although I argue that Kant’s philosophy lends strong support to abortion rights, this does not thereby entail that it allows for the complete dehumanization of the human fetus. By appealing to the writings of Kantian scholar Allen Wood, I will argue that a fetus’ status as a potential person does render it worthy of some degree of respect and moral value.